(untitled) (Veterinary Science, 2018)
By the end of the 40s´ in the last century, antibiotics were used in animals´ diets, with the aim to increase meat, eggs and milk production. The results from the productive point of view were highly positive. However, overtime, this practice was questioned from the public health point of view due to its implications in the generation of resistance to the antimicrobial used in treatments. Thus, in 2003, the European Union started with the instructions of the prohibition of its use. With respect to poultry production, the non-therapeutic use of antimicrobial is questioned not only for diseases prevention (profilaxis) but for the growth stimulation as well, what means to administer sub-therapeutic doses to animals generally through feed with the purpose of increasing their productivity and growth rate. The current challenge is to find compounds which achieve the same beneficial results in the production as the antimicrobial in growth promotion without adverse effects for such use